2020
DOI: 10.3892/wasj.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of genetics in childhood acute lymphoblastic leukemia (Review)

Abstract: Single nucleotide polymorphisms (SNPs), the most common type of genetic variation, are important for the study of human diseases. Genome-wide association studies (GWAS) have revealed specific gene polymorphisms, among hundreds of polymorphisms, that are associated with a number of diseases. Leukemia is one of these human pathologies, while acute lymphoblastic leukemia (ALL) is the most common type of cancer affecting children and adolescents. Despite progress being made in survival rates during over the past d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…4 , 14–25 GSTM1 polymorphism has shown increased risk of developing ALL in children while GSTT1 was found not to predispose to childhood ALL. 26 Additionally, patients with combined genotype ( GSTT1 null and GSTM1 null) were found to be at slight increased risk of relapse. 27 In a meta-analysis of 30 published case control studies, significantly increased risk of ALL showed association with GSTM1 and GSTT1 null genotypes {pooled ORs 1.24 (95% CI 1.17–1.31) and 1.30 (95% CI 1.06–1.60), respectively}.…”
Section: Introductionmentioning
confidence: 99%
“…4 , 14–25 GSTM1 polymorphism has shown increased risk of developing ALL in children while GSTT1 was found not to predispose to childhood ALL. 26 Additionally, patients with combined genotype ( GSTT1 null and GSTM1 null) were found to be at slight increased risk of relapse. 27 In a meta-analysis of 30 published case control studies, significantly increased risk of ALL showed association with GSTM1 and GSTT1 null genotypes {pooled ORs 1.24 (95% CI 1.17–1.31) and 1.30 (95% CI 1.06–1.60), respectively}.…”
Section: Introductionmentioning
confidence: 99%
“…Recent gene association studies that examined cancer risk have focused on the effects of single-nucleotide polymorphisms (SNPs) of genes involved in the regulation of inflammation and tumor suppression, such as chemokines, TP53 and cytochrome P450s (CYPs) (8,9). Chemokines induce the migration of endothelial and tumor cells and consequently influence distal metastasis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several gene polymorphism have been investigated concerning susceptibility to ALL including SNPs of carcinogen metabolism genes, folate metabolism genes, DNA repair genes, regulators of lymphoid cell differentiation, tumor suppressors ,transcriptional factors and chemokines, in addition ,various SNPs participating in the metabolism of antileukemic agents inducing therapy toxicity , discontinuation of therapy with risk of relapse (Kampouraki et al,2020).…”
Section: Introductionmentioning
confidence: 99%